The National Board for Research and Innovation (NBRI) is the principal advisory body for defining Research and Innovation (R&I) strategy in Cyprus - Anayiotos, Andreas (My University, 2026)
The Board undertakes the promotion and implementation of national R&I Strategy. It has a monitoring and guiding role in the implementation of the new R&I governance structure, it submits suggestions and proposals on strategic issues and monitors the implementation of policies adopted at policy level. NBRI members are appointed by the Council of Ministers, based on a proposal submitted by the Minister of Finance and serve for a 3-year term, subject to renewal. Board members include highly regarded individuals, from the public or private sector, with expertise in the fields of research, innovation and entrepreneurship. Participation to the Board is possible for individuals from Cyprus or abroad, including non-Cypriot nationals. NBRI meets regularly, usually every two months, and is supported by the Chief Scientist and the Directorate for R&I (DG EPCD), which serves as the Board Secretariat. Within the context of the “Innovate Cyprus Strategy”, the Board has adopted the vision for Cyprus to become a dynamic and competitive economy, driven by research, scientific excellence, innovation, technological development and entrepreneurship, and a regional hub in these fundamental areas. It is committed to working together with the Government and stakeholders of the Republic towards sustainable economic development and social prosperity, built on the foundations of research and innovation. January 2019 – January 2022
Keywords: Sciences